2018
DOI: 10.1002/14651858.cd005263.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Supervised exercise therapy versus home-based exercise therapy versus walking advice for intermittent claudication

Abstract: of findings for the main comparison. Supervised exercise therapy versus home-based exercise therapy for intermittent claudication Supervised exercise therapy versus home-based exercise therapy for intermittent claudication Patient or population: patients with intermittent claudication Setting: community-based/hospital-based Intervention: supervised exercise therapy Comparison: home-based exercise therapy Anticipated absolute effects* (95% CI) Outcomes Cochrane Library Trusted evidence. Informed decisions. Bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(157 citation statements)
references
References 150 publications
6
132
1
5
Order By: Relevance
“…During quarantine we must promote physical activity at home. Little information is available on effects of homebased physical activity on chronic disease [32][33][34]. Despite physical activity being defined mandatory for cardiovascular prevention, guidelines do not contain home-based physical activity indications [35].…”
Section: What Must Be Done To Prevent Increase Of Obesity and Of Cardmentioning
confidence: 99%
“…During quarantine we must promote physical activity at home. Little information is available on effects of homebased physical activity on chronic disease [32][33][34]. Despite physical activity being defined mandatory for cardiovascular prevention, guidelines do not contain home-based physical activity indications [35].…”
Section: What Must Be Done To Prevent Increase Of Obesity and Of Cardmentioning
confidence: 99%
“…A systematic review published in 2013 suggested that there was only low‐level evidence supporting the benefit of home exercise programmes and more robust trials were needed. A recent Cochrane review also suggested that home exercise had no benefit over walking advice alone and was less effective than supervised exercise in improving walking performance in patients with PAD. Since publication of these systematic reviews, more randomized trials of home exercise programmes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exercise intervention with supervised exercise or home-based exercise (Hageman, Fokkenrood, Gommans, Houten, & Teijink, 2018) and those with different exercise durations (Sweegers et al, 2018) have been reported positive effect on quality of life.…”
mentioning
confidence: 99%